The impact of social capital and social environmental factors on mental health and flourishing: the experiences of asylum-seekers in France - Maria De Jesus; Bronwyn Warnock; Zoubida Moumni; Zara Hassan Sougui; Lionel Pourtau (Conflict and Health, 2023)
Abstract Background There is growing interest on how social capital and related social environmental factors impact overall population health and well-being. The nature of asylum-seekers’ social environment alters once they migrate to a new context and these changes influence their mental health and well-being. However, there is limited scholarship on how these social environmental factors impact the mental health, well-being, and capacity to flourish of asylum-seekers. Methods The aim of the study, therefore, was to examine how specific social environmental factors—social networks, social support, and social cohesion at various levels (micro, meso, and macro)—influence the mental health, well-being, and capacity to flourish of asylum-seekers in France. In collaboration with a community-based organization, we used a qualitative research design to conduct 120 semi-structured interviews with asylum-seekers in France. Results The emerging salient themes depicted how the asylum-seekers’ usual informal social networks comprised of family and friends had been disrupted since they migrated to France, which impacted their mental health and well-being. Conversely, staying connected with their informal transnational social networks via social media and developing ties with new local informal and formal social networks allowed them to receive different forms of social support, and buffered some of the negative mental health consequences. However, the lack of social cohesion due to a lack of belonging, marginalization, and current harmful migration-related policies impeded asylum-seekers’ capacity to flourish. Conclusion While social support derived from social networks buffered some negative impacts on mental health and well-being, the overall lack of social cohesion ultimately impeded asylum-seekers’ capacity to flourish within their host communities, which was further exacerbated by harmful migration policies of exclusion within France. Introducing more inclusive policies related to the governance of migration and an intersectoral approach that views health in all policies is key to promoting social cohesion and flourishing among asylum-seekers in France.